2019
DOI: 10.3390/molecules24193460
|View full text |Cite
|
Sign up to set email alerts
|

The Microenvironment in Immobilized Enzymes: Methods of Characterization and Its Role in Determining Enzyme Performance

Abstract: The liquid milieu in which enzymes operate when they are immobilized in solid materials can be quite different from the milieu in bulk solution. Important differences are in the substrate and product concentration but also in pH and ionic strength. The internal milieu for immobilized enzymes is affected by the chemical properties of the solid material and by the interplay of reaction and diffusion. Enzyme performance is influenced by the internal milieu in terms of catalytic rate (“activity”) and stability. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 86 publications
(203 reference statements)
0
59
0
6
Order By: Relevance
“…For instance, ionic strength affects the conformational stability and folding/unfolding behavior of highly charged proteins through charge screening, as detected by changes in fluorescence resonance energy transfer (FRET) efficiency [ 5 ] or a ligand-induced conformational change in a multidomain protein as determined from intramolecular bioluminescence resonance energy transfer (BRET) assays [ 6 , 7 , 8 , 9 , 10 ]. Furthermore, ionic strength is also known to affect enzymatic activity [ 11 ], aggregation and gel formation upon protein unfolding [ 12 ], the assembly of disease-causing amyloids [ 13 , 14 ], or the binding affinity and fluorescence intensity of amyloid-specific dye [ 15 ]. Similarly, the higher order assembly of the purified Caenorhabditis elegans LAF-1 protein formed by phase separation could be altered by changes in the concentration of sodium chloride in the solution [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, ionic strength affects the conformational stability and folding/unfolding behavior of highly charged proteins through charge screening, as detected by changes in fluorescence resonance energy transfer (FRET) efficiency [ 5 ] or a ligand-induced conformational change in a multidomain protein as determined from intramolecular bioluminescence resonance energy transfer (BRET) assays [ 6 , 7 , 8 , 9 , 10 ]. Furthermore, ionic strength is also known to affect enzymatic activity [ 11 ], aggregation and gel formation upon protein unfolding [ 12 ], the assembly of disease-causing amyloids [ 13 , 14 ], or the binding affinity and fluorescence intensity of amyloid-specific dye [ 15 ]. Similarly, the higher order assembly of the purified Caenorhabditis elegans LAF-1 protein formed by phase separation could be altered by changes in the concentration of sodium chloride in the solution [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes can be precipitated or denatured by the action of salts, solvents, and other reagents. Catalytic activity is the key performing parameter of any enzymatic process and depends solely on the concentrations of the substrates and the product, as well as on the pH and ionic strength [25]. Many studies have reported that an increase in ionic strength reduces enzyme activity [26].…”
Section: Effect Of Ionic Strength On Urease Activitymentioning
confidence: 99%
“…When the enzyme is immobilized, the affinity of the support for water can influence its catalytic activity. In this work, another possible reason for the enhanced thermal stability of the lipase immobilized on the amino-modified solid support may be due to a change in the microenvironment around the enzyme due to the presence of amino groups (Bolivar and Nidetzky, 2019). As a cationic polymer, APTES has been used to adsorb enzymes and stabilize proteins in solution, preventing oxidation, aggregation, and supports coated with APTES have been used to stabilize multimeric enzymes, preventing the dissociation of subunits (Fernandez-Lafuente, 2009;Aissaoui et al, 2013).…”
Section: Thermal Stabilitymentioning
confidence: 99%